Tumor necrosis factor-alpha gene and protein expression in adult feline myocardium after endotoxin administration. - Kapadia, S (1995)
TNF alpha mRNA and protein biosynthesis were examined in the adult feline heart after stimulation with endotoxin. When freshly isolated hearts were stimulated with endotoxin in vitro, de novo TNF alpha mRNA expression occurred within 30 min, and TNF alpha protein production was detected within 60-75 min; however, TNF alpha mRNA and protein production were not detected in diluent-treated hearts. Immunohistochemical studies localized TNF alpha to endothelial cells, smooth muscle cells, and cardiac myocytes in the endotoxin-treated hearts, whereas TNF alpha immunostaining was absent in the diluent-treated hearts. To determine whether the cardiac myocyte was a source for TNF alpha production, two studies were performed. First, in situ hybridization studies, using highly specific biotinylated probes, demonstrated TNF alpha mRNA in cardiac myocytes from endotoxin-stimulated hearts; in contrast, TNF alpha mRNA was not expressed in myocytes from diluent-treated hearts. Second, TNF alpha protein production was observed when cultured cardiac myocytes were stimulated with endotoxin, whereas TNF alpha protein production was not detected in the diluent-treated cells. The functional significance of the intramyocardial production of TNF alpha was determined by examining cell motion in isolated cardiac myocytes treated with superfusates from endotoxin- and diluent-stimulated hearts. These studies showed that cell motion was depressed in myocytes treated with superfusates from the endotoxin-treated hearts, but was normal with the superfusates from the diluent-treated hearts; moreover, the negative inotropic effects of the superfusates from the endotoxin-treated hearts could be abrogated completely by pretreatment with an anti-TNF alpha antibody. Finally, endotoxin stimulation was also shown to result in the intramyocardial production of TNF alpha mRNA and protein in vivo. Thus, this study shows for the first time that the adult mammalian myocardium synthesizes biologically active TNF alpha.